Developing Authentic Assessment for Differentiated English Learning at SMPN 3 Banyuwangi - Salsabila Rizki Ayu Sanara; Arin Inayah; Andre Luis Hasiminto; Devina Salsabila Zahro (LUNAR, 2026)
This study aims to develop and examine the feasibility of the authentic assessment to support differentiated learning instruction in English classrooms at SMPN 3 Banyuwangi. In this study, the researcher only uses 3 phases of ADDIE, namely: analysis, design, and development phase. Two types of authentic assessments were developed: video project and infographic project assessments, along with their rubrics., namely: video project assessment, and infographic project assessments and its rubrics. The validation results showed scores of 80.42% from experts and 99.41% from English teachers. In a small group trial, researcher used 6 students as respondents, and from the result of students' evaluation 97,226% for video project assessment and 86,67% for infographic project assessment. From the students' evaluation known as the video and infographic.The evaluation results after the small group trial show that the assessment products studyers have made are very feasible. So, the authentic assessment products, in the form of video project assessments and infographic project assessments, along with their rubrics, can be used in the learning activities.